2020
DOI: 10.1371/journal.pone.0234627
|View full text |Cite|
|
Sign up to set email alerts
|

Cuscuta seeds: Diversity and evolution, value for systematics/identification and exploration of allometric relationships

Abstract: Cuscuta (dodders) is a group of parasitic plants with tremendous economic and ecological significance. Their seeds are often described as "simple" or "unspecialized" because they do not exhibit any classical dispersal syndrome traits. Previous studies of seed morphology and/or anatomy were conducted on relatively few species. We expanded research to 101 species; reconstructed ancestral character states; investigated correlations among seed characters and explored allometric relationships with breeding systems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 97 publications
(139 reference statements)
0
14
0
Order By: Relevance
“…We also speculate that C. campestris , a naturalized invader, could be predominantly propagating through seed, hence enhanced mixing among populations, whereas C. reflexa may be largely spreading via vines although this remains to be confirmed. C. reflexa has larger seeds than C. campestris , although previous researchers found no evidence of any association between seed size and geographical distribution range among members of the genus Cuscuta (Olszewski et al, 2020). Future investigations are expected to elucidate the relationship between reproductive plasticity and the observed genetic variability in Cuscuta spp.…”
Section: Discussionmentioning
confidence: 87%
“…We also speculate that C. campestris , a naturalized invader, could be predominantly propagating through seed, hence enhanced mixing among populations, whereas C. reflexa may be largely spreading via vines although this remains to be confirmed. C. reflexa has larger seeds than C. campestris , although previous researchers found no evidence of any association between seed size and geographical distribution range among members of the genus Cuscuta (Olszewski et al, 2020). Future investigations are expected to elucidate the relationship between reproductive plasticity and the observed genetic variability in Cuscuta spp.…”
Section: Discussionmentioning
confidence: 87%
“…Cuscuta xanthochortos occurs mainly in regions having a subtropical climate, and the new record of this species in the tropical Central-Western region of Brazil (which has a tropical climate) was found in an urban garden, where the species was likely introduced (Olszewski et al 2020). The new record of C. platyloba suggests that this species probably occurs throughout the Brazilian territory; however, as with other Cuscuta species, there has been underreporting of occurrences.…”
Section: Discussionmentioning
confidence: 95%
“…However, Cuscuta is currently included in the family Convolvulaceae based on molecular phylogenetic studies that have shown the genus is nested within the morning glories family (Stefanovic et al 2002;Stefanovic and Olmstead 2004). Also, Cuscuta has strong affinities with Convolvulaceae based on their flowers (Wright et al 2011(Wright et al , 2012, fruits (Ho and Costea 2018), and seeds (Olszewski et al 2020). Yuncker (1932) conducted a worldwide taxonomic revision of Cuscuta, providing an infrageneric classification as well as descriptions and illustrations for all the species.…”
Section: Introductionmentioning
confidence: 99%
“…One such role might be to prevent lipid peroxidation by exerting their (pro)antioxidative activities 33 , thereby preserving storage resources in oil bodies for biogenesis in the next generation. This trait conferred by seed lignans seems also to be bene cial for survival of Cuscuta seedlings, which entirely rely on the nutritive reserves stored in the endosperm until they start sucking nutrition from host plants via haustoria 50 . Furthermore, a sterol-binding dehydrogenase found in oil bodies, known as steroleosin (Sol), is widespread in seed plants including gymnosperms, and is involved in germination and development by regulating phytohormone sensitivity 51,52 .…”
Section: Presence Of Both Pss and Sol-b In Seedsmentioning
confidence: 99%